A química dos liquens - Honda, Neli Kika; Vilegas, Wagner [UNESP] (Sociedade Brasileira de Química, 1999)
Lichens are symbiotic associations between fungi and algae and/or cyanobacteria. They produce common intracellular products including proteins, amino acids, polyols, carotenoids, polysaccharides and vitamins. The secondary metabolites found in lichens are phenolics which accumulate either on the cortex or on the cell walls of medullary hyphae and they are mainly acetyl-polimalonyl pathway derivatives. Polysaccharides, proteins and secondary metabolites produced by lichens have attracted the attention of investigators due their biological activities. This revision coments about the biosynthetic origin and structures of the principal classes of compounds produced by these organisms.
The chemistry of lichens
Keywords: lichens; liquenic compounds; chemotaxonomy